Justice civile et communauté rurale au Québec, 1880-1920 - Normand, Sylvio (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1984)
At the turn of the century, civil justice in rural communities was organized into three non-judicialized instances : 1) the Commissioners' Court, 2) the Court of Justices of the Peace and 3) Conciliation measures. In this paper the institutional characteristics of these three community-type instances are examined. A study of available judicial statistics indicates that the level of activity of these instances went through a pronounced decline during the period between 1880 and 1920, specifically because of the high inflation rate. A brief study of judicial records of the Commissioners' Court of Saint-Raymond de Portneuf makes it possible to draw a profile of those who came under the jurisdiction of this kind of court. An examination of legal commentary and judgements on applications for the writ of certiorari reveals the perception that the legal world then had of rural justice.